IMPROVING ACCESS TO ENVIRONMENTAL INFORMATION FOR THE SUBJECTS OF TAX RELATIONS - Zvereva, Anna; Akhmadeev, Ravil; Morozova, Tatiana; Bykanova, Olga; Avvakumova, Irina (International Multidisciplinary Scientific GeoConference SGEM, 2020)
The world practice of taxation shows that tax policy in most cases, when introducing environmental taxes, pursues the main goal of protecting the eco- system from pollution. This applies both to natural resources and to the conservation of aquatic bio resources, also considering the impact of the extinction factor of endangered species, listed in the state registers of flora and fauna. In this regard, each state independently determines the scope of environmental taxation on its territory. At the same time, it is important to follow a general approach to establishing mandatory elements of taxation, including the composition and structure of the tax base and the rates used (specific, ad valorem or combined). The study on analyzing tax revenues to the budget in the context of excisable goods collected in Russia and the Czech Republic for the tax periods of 2014-2018 has been conducted. It confirms the postulate about the globalization of all economic processes. The study shows that the share of excise payments, which indirectly reflect the desire of the state to pursue a policy to preserve the biosphere and encourage the business community to use environmental technologies, is steadily decreasing. Using correlation analysis and linear interpolation, dependencies were obtained that describe the downward trend in environmental payments with a sufficiently high degree of probability, since the analyzed coefficients are negative. However, with a general negative trend, it should be recognized that the situation in the Russian Federation is somewhat worse than in the Czech Republic, i.e. the borders were -1.325 < -0.45. Therefore, in the modern digital world, it is necessary to take measures aimed at developing applications for taxpayers that allow real-time illustration of the share of collected environmental taxes sent to the real sector of the economy by the state, taking into account the measures targeted at protecting the eco system. At the same time, the regulatory function of taxation should be more specific about the choice of the object of taxation on the source of pollution that has a negative impact on the eco system.